Quantification of chlorophylls in leaves of 'Royal Gala' and 'Fuji' apple trees with non-destructive optical methods Quantificação de clorofilas em folhas de macieiras 'Royal Gala' e 'Fuji' com métodos ópticos não-destrutivos - Do Amarante C.V.T.* (2008)
The standard method for chlorophylls quantification in leaves is destructive and time consuming. With the development of portable equipments, chlorophylls quantification became easy, quick, and affordable for non-destructive assessment at the field. Chroma meters can also be used to assess non-destructively plant tissues color and, therefore, to quantify chlorophylls in leaves. This work was carried out to evaluate the viability of using a chroma meter as an alternative to the leaf chlorophyll meter for non-destructive quantification of chlorophylls in the leaves of 'Royal Gala' and 'Fuji' apple trees. Leaves of both cultivars, with colors ranging from yellow-green (chlorotic) to dark green, were individually assessed with the chlorophyll meter (SPAD-502) and the chroma meter (Minolta CR-400, at the L, C, and ho color space), and, thereafter, destructively assessed for total chlorophyll and chlorophylls a and b. The chlorophyll meter reading and the ho/(LxC) ratio for the chroma meter increased with the increment of chlorophylls content in the leaves of 'Royal Gala' and 'Fuji' apple trees. The adjusted models between chlorophylls content versus chlorophyll meter readings and the ho/(LxC) ratio for the chroma meter had similar R2 in both cultivars. The results show that the chroma meter is a viable alternative for non-destructive assessment of chlorophylls (μg.cm -2) in apple trees, especially of chlorophyll a and total chlorophyll. For that purpose, it requires the calibration between the h o/(LxC) ratio of the chroma meter and the chlorophylls extracted from leaves of concerned cultivar.